Strategies of the Spanish press in the face of the Twitter algorithm change. Analysis of tweets published between 2018-2020 - Antonio Díaz-Lucena; Victoria Mora-de-la-Torre; Lorenzo-J. Torres-Hortelano (Communication & Society (Formerly Comunicación y Sociedad), 2022)
Twitter recently celebrated its 15th anniversary. During this period, the platform has gone through several phases, culminating in a record number of subscribers and profits in 2021. Twitter is a household name all over the world and people know what it can or cannot provide, independent of the future growth that it may experience with new investments and updates. This article aims to verify two interrelated hypotheses, namely: the Spanish press already knows how to optimise the social network Twitter, as three decades have elapsed since its launch; and, secondly, the algorithm modification implemented by Twitter in 2018 has triggered a change in the positioning of the headers studied in this social network. In order to demonstrate both, the object of analysis will be conducted by a mixed approach through quantitative statistical processes (which will study the number of impacts and retweets and likes obtained), and inductive qualitative methods such as semi-structured interviews. This multidisciplinary approach will provide a more complete and in-depth analysis of the phenomenon. The research focuses on the period between 2018 and 2020, and addresses the participation on Twitter of the four main traditional newspapers (El País, La Vanguardia, ABC and El Mundo) as well as four native digital newspapers (20 Minutos, El Español, elDiario.es and El Huffpost). The analysis comprises more than 1.5 million tweets among the eight chosen newspapers.